The political life of things: Explorations on material culture and consumption in Evangelical groups in Buenos Aires, Argentina - Algranti, Joaquin Maria (2017)
The aim of the article is to explore the material culture of Neo-Pentecostals´ mega-churches in Buenos Aires City, Argentina. In order to do this, we will reconstruct three consumers’ profile and the way that political senses are put into play. Profiles will be analyzed according to (a) the ritual context that eases consumption through specific institutions; (b) the chosen objects and (c) the political meanings that is inferred from the uses and understandings of them. This article is divided into three parts. In the first one, we are going to briefly develop the methodological framework and introduce the concepts of megachurch and material culture. In the second one, we will empirically study three religious consumption itineraries that describe different modalities of participation in the internal life of temples. Lastly, we are going to explore the political senses related to cultural commodities of large Evangelical organizations.